2018
DOI: 10.1186/s12884-018-1828-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal supplement beverage with and without probiotics during pregnancy and lactation on maternal and infant health: a randomized controlled trial in the Philippines

Abstract: BackgroundAdequate nutrition is essential during pregnancy and lactation to provide sufficient energy and nutrients to meet the nutritional requirements of the mother, fetus and infant. The primary objective of this study was to assess the effect of a maternal nutritional supplement enriched with probiotics during pregnancy and early lactation on the incidence of infant diarrhea.MethodsHealthy, pregnant (24–28 weeks gestation) women were randomized 1:1:1 to receive either no supplement or two servings per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The adverse outcomes evaluated were maternal health in one trial [ 187 ]; pregnancy-related or fetal adverse outcomes in three trials [ 187 , 188 , 189 ]; fetal and/or neonatal anthropometry in 10 trials [ 187 , 188 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ]; infections, including severe infections in eight trials [ 196 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ]; allergic disorders in three trials [ 203 , 205 , 206 ]; gastrointestinal effects in 10 trials [ 187 , 190 , 191 , 192 , 193 , 196 , 197 , 200 , 203 , 205 ]; and noncommunicable diseases in one trial [ 194 ]. Only five studies evaluated the safety during pregnancy [ 187 , 188 , 189 , 190 , 206 ]. The obstetric variables analyzed by these studies were miscarriage before 22 weeks, caesarean delivery, gestational diabetes, prematurity, fetal growth, Apgar score, birth weight, birth length, head circumference at birth, gestational hypertensive disorders, postpartum hemorrhage, maternal weight gain, and tolerance of the product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse outcomes evaluated were maternal health in one trial [ 187 ]; pregnancy-related or fetal adverse outcomes in three trials [ 187 , 188 , 189 ]; fetal and/or neonatal anthropometry in 10 trials [ 187 , 188 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ]; infections, including severe infections in eight trials [ 196 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ]; allergic disorders in three trials [ 203 , 205 , 206 ]; gastrointestinal effects in 10 trials [ 187 , 190 , 191 , 192 , 193 , 196 , 197 , 200 , 203 , 205 ]; and noncommunicable diseases in one trial [ 194 ]. Only five studies evaluated the safety during pregnancy [ 187 , 188 , 189 , 190 , 206 ]. The obstetric variables analyzed by these studies were miscarriage before 22 weeks, caesarean delivery, gestational diabetes, prematurity, fetal growth, Apgar score, birth weight, birth length, head circumference at birth, gestational hypertensive disorders, postpartum hemorrhage, maternal weight gain, and tolerance of the product.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies used single-strain probiotics ( Lactobacillus rhamnosus GG, Lactobacillus reuteri DSM 17938, Bifidobacterium lactis CNCM I-3446, Bifidobacterium longum subsp. infantis CECT7210 and EVC001) [ 192 , 193 , 195 , 196 , 197 , 200 , 202 , 203 , 205 ] and nine more used a combination of probiotics [ 187 , 188 , 189 , 190 , 191 , 194 , 201 , 204 , 206 ]. The species of probiotics used most often were Lactobacillus rhamnosus, Bifidobacterium infantis, Lactobacillus reuteri , and Bifidobacterium lactis .…”
Section: Resultsmentioning
confidence: 99%
“…PTB rates were reported as a secondary outcome in two studies testing different combinations of probiotics. Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 were tested in Finland [146], and Lactobacillus rhamnosus LPR and Bifidobacterium lactis NCC 2818 in the Philippines [147]. Both studies found PTB rates much lower than national averages reported by WHO, 1.7% vs. 5.5% in Finland and 2.4% vs. 15% in the Philippines [8].…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, additional energy and nutrients lead to gains in perinatal outcomes across the study sample (eg, Huynh, Tran, Nguyen, Berde, & Low, ). In others, they do not (eg, Mantaring et al, ; Stevens et al, ). Most recent studies in diverse populations, however, point to the importance of maternal and ecological characteristics in mediating the impact of supplementation.…”
Section: Prenatal Supplementation Studies: Contingent Outcomesmentioning
confidence: 99%
“…Just as biological anthropologists are expanding the scope of life history theory to account for the costs and benefits of immune activation (McDade, ; Shattuck‐Heidorn, Reiches, Prentice, Moore, & Ellison, ; Urlacher et al, ), public health and nutrition researchers are pushing the frontiers of supplementation in an attempt to influence maternal immune responses and fetal immune system development through the use of probiotics (Baldassarre et al, ; Cabridain et al, ; Mantaring et al, ). This research program on prenatal interventions in the gut microbiome is in its infancy.…”
Section: Prenatal Supplementation Studies: Contingent Outcomesmentioning
confidence: 99%